OP0029 Medial meniscal root tears are associated with medial meniscal extrusion and medial tibiofemoral cartilage damage – the most study. (23rd January 2014) - Jarraya, M.; Felson, D.T.; Hayashi, D.; Roemer, F.W.; Zhang, Y.; Niu, J.; Crema, M.; Englund, M.; Lynch, J.A.; Nevitt, M.C.; Torner, J.; Lewis, C.E.; et al.
Abstract : Background: The meniscal root is a ligamentous structure that anchors the posterior horn of the meniscus to the tibial plateau. The association of isolated meniscal root tears with progression of osteoarthritis or cartilage loss has not been examined. Objectives: To assess the cross sectional association of medial meniscal root tears with prevalent medial tibiofemoral cartilage damage and medial meniscal extrusion in subjects with radiographic osteoarthritis. To assess if isolated medial meniscal root tears increase the risk of incident/progressive cartilage damage in the medial tibiofemoral compartment at 30-month follow up. Methods: The Multicenter Osteoarthritis (MOST) Study is a longitudinal observational study of subjects with or at risk for knee osteoarthritis. 594 knees were randomly selected for this study. Cartilage damage was scored according to WORMS. Prevalent cartilage damage was defined as any score ≥2. Longitudinal progression of cartilage damage was studied for 548 patients who had follow up MRIs read, and was defined as a half grade or more increase from baseline to follow-up including incident cartilage damage. Meniscal extrusion was recorded as present or absent. "Isolated meniscal root tear" was defined as the presence of a root tear without any additional meniscal pathology (WORMS1-4). We studied 3 groups: the Exposed Group: knees with an isolated medial meniscal root tear; referent group A: knees without root tears but with other meniscal pathology (scores 1-4); and referent group B: without root tear or meniscal pathology. In the longitudinal analysis, we calculated relative risks (RR) of incident/progressing cartilage damage comparing the exposed group to referent groups A and B. Results: For cross-sectional analysis 594 knees were included (64.1% women, mean age 62.8±7.9, mean BMI 30.9±5.2). There were 37 knees in the exposed group, 293 in referent group A and 264 in referent group B. Exposed knees showed higher prevalence of meniscal extrusion than referent group B (91.9% vs. 60.7%, p<0.0001). Prevalence of cartilage damage was also higher in the exposed group than in group B (97.3% vs 63.7%, p<0.0001) but not group A (97.3% vs 95.2%, p=0.057). Longitudinal analyses included 548 knees; 33 knees in the exposed group, 270 in group A and 245 in group B. Using group B as the reference, adjusted RR of cartilage loss was 2.04 (95%CI 1.19 - 3.49) for the exposed group. Group A also had a higher risk of cartilage loss than Group B (RR =1.84; 95% CI 1.32 – 2.58). Conclusions: Isolated medial meniscal root tears are strongly associated with medial meniscal extrusion. Isolated meniscal root tears increase the risk of cartilage loss longitudinally. Disclosure of Interest: M. Jarraya: None Declared, D. T. Felson: None Declared, D. Hayashi: None Declared, F. W. Roemer Shareholder of: Boston Imaging Core Lab (BICL), LLC., Consultant for: Merck Serono, NIH, Y. Zhang: None Declared, J. Niu: None Declared, M. Crema: None Declared, M. Englund: None Declared, J. A. Lynch: None Declared, M. C. Nevitt: None Declared, J. Torner: None Declared, C. E. Lewis: None Declared, A. Guermazi Shareholder of: Boston Imaging Core Lab (BICL), LLC., Consultant for: Astra Zeneca, Genzyme, Novartis, Stryker, Merck Serono